(untitled) (Global Journal of Science Frontier Research, 2016)
As a new technical approach, a hydraulic and magnetic clamp device was attempted to realize a magnetic clamp crane system that uses 8 simultaneously actuating individual hydraulic cylinders. Through this approach, a Sr type of ferritic permanent magnet(SrO ․ 6Fe 2 O 3 ), not the previously employed electro-magnet, was utilized for the purpose of lifting and transporting the heavy weighted and oversized curved steel plates used for manufacturing the ships. This study is aimed at manufacturing and developing the hydraulic magnetic clamp prototype, which is composed of three main parts -the base frame, cylinder joint, and magnet joint -in order to safely transport such curved steel plates. Furthermore, this research was pursued to conduct a performance evaluation as to the prototype manufacture and acquire the planned quantity value and the development purpose items.